Enhancing Teacher Competence Through Professional Education Programs - Muhammad Zidni Fadhlurrahman; Ita Nurmalasari; Rosyidah Nur Lailiyah (Al-Qalam Institue, 2026)
This study aims to describe strategies for improving teacher competence through the Teacher Professional Education Program (PPG) at MTs Pangeran Diponegoro. Employing a qualitative case study design, data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using Miles, Huberman, and Saldaña’s interactive model. The study is grounded in national teacher competency regulations, including Law No. 14 of 2005, Government Regulation No. 19 of 2005, Ministerial Regulation No. 16 of 2007, and the objectives of PPG as outlined in Ministerial Regulation No. 87 of 2013. The findings indicate that the PPG program effectively enhances teachers’ pedagogical, professional, social, and personal competencies. Participants demonstrated more systematic lesson planning, stronger mastery of subject matter, improved communication and collaboration skills, and increased professional commitment. Institutional support from the madrasah played a significant role in reinforcing these improvements, although challenges such as limited time allocation and workload constraints persisted. These findings imply that sustained institutional support and flexible implementation strategies are essential to maximize the long-term impact of teacher professional education programs on instructional quality.